Hubungan Tekanan Cuff Endotrakeal Terhadap Nyeri Tenggorokan Pasca Operasi Pada Pasien Odontektomi Di RSUD Dr. Tjitrowardojo Purworejo - Amanda Aulia Malika; Astika Nur Rohmah; Ririn Zuhairini (Akademi Keperawatan Yarsi Samarinda, 2026)
Background: The use of an Endotracheal Tube (ETT) during general anesthesia may cause Post Operative Sore Throat (POST). In odontectomy patients, the risk is higher because the surgical intervention is performed in the oral and airway region. Objective: To determine the correlation between ETT Cuff pressure and postoperative sore throat in odontectomy patients at RSUD Dr. Tjitrowardojo, Purworejo. Methods: A quantitative study with a cross-sectional design was conducted among 67 patients selected by incidental sampling. Data were collected using an ETT Cuff pressure observation sheet and a postoperative sore throat scale. Spearman Rank test was used for analysis. Results: The majority of respondents had normal ETT Cuff pressure (56.7%) and experienced moderate sore throat (43.3%). The Spearman Rank test yielded a p-value of 0.000 (p=0.05) with a correlation coefficient of 0.468, indicating a significant relationship with moderately strong positive correlation. The higher the ETT Cuff pressure, the higher the level of sore throat. Conclusion: There is a correlation between ETT Cuff pressure and postoperative sore throat in odontectomy patients at RSUD Dr. Tjitrowardojo, Purworejo.